2016
DOI: 10.1159/000444447
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Age Differentially Mediates the Calcium-Binding Protein Parvalbumin in the Rat: Evidence for a Selective Decrease in Hippocampal Parvalbumin Cell Counts

Abstract: Local circuit GABAergic neurons, including parvalbumin (PV)-containing basket cells, likely play a key role in the development, physiology, and pathology of neocortical circuits. Regionally selective and well-defined decreases in PV have been described in human postmortem schizophrenic brain tissue in both the hippocampus and prefrontal cortex. Animal models of schizophreniform dysfunction following acute and/or chronic ketamine treatment have also demonstrated decreases in PV expression. Conflicting reports w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…The present work supports previous studies detailing a developmentally-dependent normative decrease in PV cell count within all sub-regions of the HPC (CA1, CA3, DG), but not within adjacent cortical regions in control rats (Honeycutt et al, 2016). Importantly, this work is the first to detail a novel dissociation between the effects of chronic KET administration on PV cell count based on age of treatment and anatomical region, without regard to time of tissue collection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present work supports previous studies detailing a developmentally-dependent normative decrease in PV cell count within all sub-regions of the HPC (CA1, CA3, DG), but not within adjacent cortical regions in control rats (Honeycutt et al, 2016). Importantly, this work is the first to detail a novel dissociation between the effects of chronic KET administration on PV cell count based on age of treatment and anatomical region, without regard to time of tissue collection.…”
Section: Discussionsupporting
confidence: 90%
“…Findings indicating developmental changes in PV from young to adult rodents provide a compelling argument for considering age as a factor. Specifically, our group and others have presented evidence of decreased PV within the HPC in adult compared to young rodents (de Jong et al, 1996;Honeycutt et al, 2016). These findings indicate a distinct developmental trajectory of PV phenotype which likely influences the efficacy and/or outcomes of experimental treatments based on subject age.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…It has been proposed that the differences in theta dynamics along the septo-temporal axis result from distinct innervation, on the one hand, and from specific intrinsic properties of hippocampal neurons, on the other hand. Cholinergic projections of different origin in the dHP and i/vHP ( Stewart and Fox, 1990 ; Amaral et al, 2007 ) as well as maturational differences in the intrinsic resonant properties of hippocampal neurons and notable gradients of parvalbumin immunoreactivity along the septo-temporal axis ( Honeycutt et al, 2016 ) may contribute to the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in dendritic branching of PV+ interneurons at puberty could result in increased inhibitory synaptic input to the pyramidal cells and may underlie the observed increase in phasic current at puberty, although other possibilities such as presynaptic effects and altered PV+ activity, as discussed below, may play a role. Increases in PV expression have been reported in the hippocampus across development (Wu et al, 2014) unaccompanied by increases in interneuron numbers (Honeycutt et al, 2016), although puberty has not been investigated until the present study. Our results showing an increase in dendritic branching at puberty may underlie these findings.…”
Section: Discussionmentioning
confidence: 83%